Implementación, Instalación, montaje y monitoreo de un sistema fotovoltaico para riego del cultivo en la finca La Vega del barrio Chaquino, parroquia Bolaspamba, cantón Zapotillo. - Rogel Ramírez, Willams Leonardo (2012)
The systems of photovoltaic pumping begin to have, behind yes a history of which is possible to extract successful summations that they serve as utility for their evolution in the future. The execution of this project ingenieril, was born as a prototype without knowing the suitable sector to develop it. In the first place you carries out, determining the sectors or communities in which one could efectivizar this project. In function of the Solar Atlas, the good area of the Region South beneficiary for the same one is the canton Zapotillo. By means of having traveled by the parishes of Lemons, Progress, Shoulder blades and Bolaspamba and with the contribution of the rural organizations, he was solved that the community to carry out this initiative is Chaquino and the organization that he would give the collateral signature it would be the Cantonal Union of Rural Organizations UCOCZ. Previously to start this project, you design a small model before determining the influence area and the acquisition of teams made it to him in function of that designed. In the face of the necessity of the community of endowing of water for watering in a property of a hectare and he mediates, it was resized and you readjusts with existent teams in the project MIPRO. On the other hand the proprietors of the denominated property “La Vega” located 2 kilometers of Chaquino, they built a concrete tank whose capacity is of 21,65 m^3, and they reconditioned the shallow well the same one that has a capacity of 17,63 m^3 and volume of water of 6 m^3, this well it is located near the gulch Cazaderos. In the same way this context, seeks to study the problem associated to the use of photovoltaic solar systems and to propose recommendations about its design and experiences in its installation. In particular, this work seeks to impel the benefits that offer us this type of systems, the same ones that can be used in farms, properties, etc. where it would be needed to take water, allowing a long term economic saving.